Empowering mothers in education: An assessment of the impact of enhanced maternal literacy approach for teaching essential skills - Baraguir, Hanissa F.; Alava, Mary Thallasah Nicole T.; Minandang, Bai Tanto D.; Agao-Agao, Ana Margarita; Gumogda, Pinky A.; Jr., Datulabi P. Untong; Edris, Adelaida A.; Malim, Usman B.; Siocon, Ana Trisha F.; Blah, Sadat G.; et al. (Edelweiss Applied Science and Technology, 2025)
This study examined the effectiveness of two Enhanced Maternal Literacy Approaches (EMLA) using the Montessori method and the Reggio Emilia method in improving children’s foundational skills in reading, writing, and arithmetic (3Rs). A quasi-experimental design with pre- and post-tests was employed, involving fifty (50) mothers and their children in a rural community in Maguindanao del Norte. Twenty-five mothers were trained to implement the Montessori EMLA, while the other twenty-five adopted the Reggio Emilia EMLA. The children’s performances were assessed using the Early Grade Reading Assessment (EGRA), Early Grade Writing Assessment (EGWA), and Early Grade Mathematics Assessment (EGMA). Results revealed that both approaches significantly enhanced children’s 3Rs performance. The Montessori group showed greater improvement in writing skills, while the Reggio Emilia group demonstrated stronger gains in arithmetic. No significant difference was observed in reading performance between the two groups. The findings indicate that both approaches are effective, but each possesses distinct strengths that complement one another. The study highlights the potential of structured maternal literacy interventions in enhancing children’s foundational skills and recommends further integration of both approaches in early childhood education programs.